Conversations about Death and Dance: the threads weaved by Thanatos and Terpsichore - Albano Viana, Ana Cláudia; da Nóbrega, Terezinha Petrúcia (Revista Brasileira de Estudos da Presença, 2022)
The object of the essay is the relationship between dance and death, reflected from choreographic works in which we understand that dance expresses the existential condition of death in its inexorability, tragedy and poetry. In this thought, it is observed the relationship of death and life with temporality, a time created in which we can transform the body, life and death. In this perspective, we try to weave a network of meanings about this relationship, dialoguing with choreographic art and philosophy. This perception contributes to the understanding of art as an educational phenomenon by nuancing issues of existence, such as death.